Biomass distribution efficiency of rose cv. charlotte grown in soil and substrates at second production peak (2013)
Growing plants in substrates is an alternative for the productionof roses under unfavorable soil conditions. The objective of thisstudy was to determine the biomass distribution efficiency ofrose cv. Charlotte grown in soil and substrates under greenhouseconditions until second production peak. In this trial,soil and substrates with 100% burned rice husk (100BRH); 65%burned rice husk: 35% coconut fiber (65BRH); 35% burnedrice husk: 65% coconut fiber (35BRH); and 100% coconutfiber (100CF) were used. The experimental design consistedof a randomized complete block design with three repetitions.Destructive sampling was carried out using whole plants andflowering stems at previously determined bud stages. Leaf areaand dry matter in organs were measured and growth rate andphysiological indexes were calculated. The assessed variableswere fitted to logistic and exponential models. The plants grownin substrates with BRH (burned rice husk) showed similarvalues regarding dry matter and fresh weight accumulationin organs. Plants in the soil treatment were the last ones toreach the different development stages of the flowering buds,while those that were grown in 100CF were the first ones. Thetreatments 35BRH and 100CF showed less growth of floweringstems, which was expressed in terms of relative dry matterincrease per day. The plants grown in soil showed more drymatter in leaves and stems but less in flower buds. The 65BRHtreatment showed some of the highest dry matter accumulationsin leaves, stems and flower buds and also showed the highestleaf area ratio, leaf weight ratio, and specific leaf area values.